2019
DOI: 10.1123/jsr.2017-0306
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping Improves Perceptions of Pain and Function of Patients With Knee Osteoarthritis: A Randomized, Controlled Trial

Abstract: Wearing kinesio tape for three consecutive days had beneficial effects regarding self-reported clinical outcomes of pain, joint stiffness and function. This emphasizes that kinesio taping might be an adequate conservative treatment for the symptoms of knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 42 publications
(63 reference statements)
6
45
1
1
Order By: Relevance
“…Similarly, Kaya Mutlu et al 13 reported improved flexion with no significant improvements in knee extension. Rahlf et al 9 did not find positive effect of Kinesio Taping on the ROM. The different designs of reported trials and multifarious taping applications used in the studies can be the possible reason for the diverse outcomes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, Kaya Mutlu et al 13 reported improved flexion with no significant improvements in knee extension. Rahlf et al 9 did not find positive effect of Kinesio Taping on the ROM. The different designs of reported trials and multifarious taping applications used in the studies can be the possible reason for the diverse outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Rahlf et al 9 and Öğüt et al, 10 however, reported Kinesio Taping to produce higher than sham taping improvements in functioning immediately after treatment. It is noteworthy that in these studies, the researchers used sham taping not directly on the knee joint region.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, while evidence supports combined interventions for thumb OA, we are unable to make specific recommendations regarding combined interventions for knee OA, or for other affected joints. With respect to adjunct interventions, we found evidence to support the use of tape for knee OA 21,55,57 , assistive devices for hand OA 59 , thumb splints for thumb OA 60 , manual therapy for knee OA 23,45,47,53 and neck OA 65 , acupuncture for knee OA 44 , and electrophysical agents for knee OA 19,22,48 (Tables III and IV), while conflicting evidence was found for transcranial direct current stimulation (tDCS) 30,37 (Table IV). Taken together with established clinical guidelines, our findings reinforce that these interventions should be adjuncts to accompany core recommended interventions for OA, rather than be used as standalone or key treatments 2,3,9e16 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the therapeutic efficacy of KT therapy on pain [8,[13][14][15], functional activity [8,13,16], and proprioception [17][18][19] in patients with knee OA [2,20]. However, to our knowledge there is only one study about the effect of taping on balance in patients with knee OA, that have assessed functional reach test and anterior-posterior stability of the knee following patellar taping by rigid tape and showed that adding medial patellar taping technique to the exercise physical therapy program had more significant improvement on anterior-posterior stability and functional reach test than exercise alone in patients with OA [21] also despite the different methods of knee taping there are few studies to clarify the superiority of these methods, thus the present study was carried out to investigate and compare the effect of two common kinsio taping (quadriceps muscle taping and patellar taping) for knee OA, on balance and functional performance in patients with knee OA.…”
Section: Introductionmentioning
confidence: 99%